Postoperative study of vital capacity and ventilation measurements following elective craniotomy - Sogame, Luciana Carrupt Machado; Faresin, Sonia Maria; Vidotto, Milena Carlos; Jardim, José Roberto (São Paulo Medical Journal, 2008)
CONTEXT AND ObjeCtivE: Changes in pulmonary function commonly occur after general surgery. The aims were to evaluate vital capacity, tidal volume and respiratory frequency among patients undergoing elective craniotomy and to determine possible correlations of these parameters with surgery duration and etiology for neurosurgery. DESIGN AND SETTING: Prospective, open study at a tertiary university hospital. METHODS: Twenty-six patients underwent elective craniotomy for aneurysm clipping (11) or tumor resection (15). Vital capacity (VC), tidal volume (TV), minute volume (VE) and respiratory rate were determined before the operation and on the first to fourth postoperative days. RESULTS: There were significant decreases of 25% in VC, 22% in TV and 12% in VE (p < 0.05) and no significant increase in respiratory frequency (5%) on the first postoperative day. VE returned to baseline on the second postoperative day and TV on the third postoperative day, while VC was 8% lower on the fourth postoperative day, compared with before the operation (p < 0.05). VC reduction was significantly greater in patients undergoing aneurysm clipping (43%) than in patients undergoing tumor resection (14%) when surgery duration was more than four hours (p < 0.05), with no significant change when surgery duration was less than four hours. CONCLUSION: Reductions in VC, TV and VE were observed during the postoperative period in patients undergoing aneurysm clipping or tumor resection. The reductions in VC and TV were greater in patients undergoing craniotomy due to aneurysm and with longer surgery duration.